Design, fabrication and calibration of a tall pneumatic oedometer apparatus. (15th October 2020) - Karimpour-Fard, Mehran; Zarbakhash, Shayan; Soufi, Ghazal Rezaie; Ahadi, Alireza; Naveen, B.P.
Highlights: A tall oedometer equipped with pressure cells and pore pressure transducers is made. Testing in the tall oedometer shows that significant sidewall friction is generated. The generated friction leads to unconventional vertical stress profiles in the soil. Experiments with stepwise-increasing sample heights were done to measure friction. The oedometer can measure the K0 value & estimate the Bjerrum-Burland coefficient. Abstract: In conventional oedometers, the height to diameter ratio of samples is kept small enough to minimize friction between the soil and cell walls. However, in oedometers with a higher height to diameter ratio, evaluating the effect of frictional interaction is imperative. This paper presents the development and experimental evaluation of a tall oedometer. Equipped with pore pressure transducers and lateral and normal pressure cells, this oedometer is capable of measuring pore pressure and lateral stresses. The tallness of the oedometer facilitates the evaluation of compressibility properties in highly compressible geomaterials. With the aid of the bottom load cell, the distribution of frictional stresses between the geomaterials and the walls can be measured. Experimental tests have been devised to obtain the actual vertical stress profiles, and results have been verified with analytical solutions in literature as well as numerical modeling. The experimental investigation illustrated the satisfactory performance of the equipment.